Preliminary validation study of the Portuguese version of the Functional Assessment of Cancer Therapy - Cognitive Function (FACT-Cog) – Version 3 (Journal of Statistics on Health Decision, 2021)
Introduction:The Functional Assessment of Cancer Therapy - Cognitive Function– Version 3 (FACT-Cog) [1] is one measure of a series of questionnaires dedicated to assessing other chronic illnesses and conditions under the umbrella of Functional Assessment of Chronic Illness Therapy (FACIT). FACT-Cog is one of the most well-known and widely used self-report instruments, specifically developed to evaluate cognitive complaints in cancer patients. No validity study of the Portuguese translation of this psychological assessment instrument is known, despite its clinical relevance.Cognitive impairment is one of the most frequent side effects reported by breast cancer survivors [2]. Perceived cognitive functioning (PCF) is an important outcome in research and clinical practice with this population [2]. Subjective assessment is an effective and valid approach to collect data representing patients’ PCF [3], as confirmed by objective evidence showed with neuroimaging [4]. It may also be clinically very useful to understand patient distress, perception of cognitive function and to identify patients with subtle deficits who may benefit from a neuropsychological evaluation or a more frequent monitoring [5,6].In this work, the preliminary study of the psychometric characteristics of the FACT-Cog in a sample of Portuguese breast cancer women is described, namely internal consistency and concurrent validity.Methods:This preliminary validation study was performed on a convenience sample of 73 female breast cancer survivors aged 29 to 64 years old (M=45.51 years; SD=8.59). Participants answered an online questionnaire protocol consisting of: socio-demographic and clinical questions, the FACT-Cog, and the Cognitive Functioning Subscale of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire – version 3(EORTC QLQ-C30) [7,8].This study used the licensed FACIT’s Portuguese translation of the FACT-Cog. The FACT-Cog is a 37-item self-report measure that consists of four subscales: Perceived Cognitive Impairments (PCI); Comments from Others (Oth), Perceived Cognitive Abilities (PCA) and Impact on Quality of Life (QoL). Higher scores indicate better PCF. The reliability and validity of these scores have been widely established [9,10].EORTC QLQ-C30 is a measure that assesses health-related quality of life in cancer patients. For this study, the 2 items of the subscale were used, with higher scores representing better PCF. This measure presents good psychometric properties [8].All statistical analyses were performed using the software IBM SPSS Statistics version 21.0. Descriptive statistics were calculated. Reliability was established by internal consistency analysis and validity was evaluated through construct validity. Pearson’s correlation coefficient was used to evaluate construct validity, examining the associations between the four subscale scores of the FACT-Cog and the Cognitive Functioning subscale of the EORTC QLQ-C30. All significance tests were conducted using a significance level of p
Keywords: Validation study; Preliminary results; Functional Assessment of Cancer Therapy - Cognitive Function – Version 3; FACT-Cog-v3; Perceived cognitive functioning; Cognition; Breast neoplasms; Cancer survivors